2006
DOI: 10.1086/500578
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Magnitude Distributions and Light Curves of Stripped-Envelope Supernovae

Abstract: The absolute visual magnitudes of three Type IIb, 11 Type Ib, and 13 Type Ic supernovae (collectively known as stripped-envelope supernovae) are studied by collecting data on the apparent magnitude, distance, and interstellar extinction of each event. Weighted and unweighted mean absolute magnitudes of the combined sample, as well as various subsets of the sample, are reported. The limited sample size and the considerable uncertainties, especially those associated with extinction in the host galaxies, prevent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
148
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(166 citation statements)
references
References 57 publications
16
148
2
Order By: Relevance
“…All data are plotted in the R-band except for SN 1997ef which is plotted in the V-band due to a lack of coverage in the R-band. As previously mentioned, SNe Ic are known to be a heterogeneous group both in terms of their absolute peakmagnitude range and their lightcurve shapes (see Richardson et al 2006), not to mention their spectral properties (see Sect. 3).…”
Section: Light Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…All data are plotted in the R-band except for SN 1997ef which is plotted in the V-band due to a lack of coverage in the R-band. As previously mentioned, SNe Ic are known to be a heterogeneous group both in terms of their absolute peakmagnitude range and their lightcurve shapes (see Richardson et al 2006), not to mention their spectral properties (see Sect. 3).…”
Section: Light Curvesmentioning
confidence: 99%
“…Richardson et al (2002) and Richardson et al (2006) have tentatively suggested a case for two groups of strippedenvelope SNe (SNe IIb, Ib and Ic); one normal-luminosity set with mean M V = −17.7 and an over-luminous set with mean M V = −20.08. In Fig.…”
Section: Confirming the Heterogeneity Of Sne Icmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to avoid biasing our sample against or in favor of one of the SN subtypes, we have to cut it at V HEL < 5000 km s −1 . Richardson et al (2006) produced absolute magnitudes for Ib and Ic, of −17.98 (scatter of 0.46), and −18.14 (0.48) respectively for the so-called "normal" ones. These values are similar and slightly brighter than the "normal Ibc" taken from Richardson et al (2002), so SNIb and SNIc should be biased neither against each other, nor against SNII adopting V HEL < 5000 km s −1 .…”
Section: The Supernova Samplementioning
confidence: 99%
“…Assuming the peak magnitudes to be normally distributed around the mean is consistent with observations, cf. Richardson et al (2002) and Richardson et al (2006). The range in peak absolute magnitudes considered is given by…”
Section: The Parameter Prior Distributionsmentioning
confidence: 99%